Learner’s View on English Language Teaching by Hybrid System Technology in Supporting Maritime Sector - Rikat Eka Prastyawan; Daisy Dwijati K.R; Desi Tri Cahyaningati; Perwi Darmajanti; Ika Erawati (SAGA: Journal of Technology and Information System, 2024)
Human Resource Development becomes the key to change the better condition. One of components which influence its development is by mastering the international language. Indonesia as the archipelago country must be strong on maritime sector followed by potential human resource development. One of the ways which could be done is by improving the communication skill by using English Language. English has been introduced for learners since they are in the kindergarten. They have learned English for more than 12 years after they graduate in level of Senior High School. The research question in this study was how was the learners' view on English Learning to become young generation having good communication skill? This research aimed to know the learner's view by reflecting their prior experiences in English learning that had been done. This study conducted a descriptive quantitative by using survey to get the data. The instrument of the research referred to the skill of communication components reflected to the learners' experiences in English learning process since the long period of time. There were 30 learners delivering their ideas on English learning to answer the research question. The result showed that the learners had the obstacles dominantly in linguistics, social and culture, even psychological factors. It could be concluded that becoming a good communicator by using English, it needs the exploration on the learner's view in order to omit his or her obstacle in learning or acquiring English Language. It's really hoped that this research could give the discourse for English learners and teachers so young generation could have good communication skill by using English to support the maritime sector as the nations in archipelago country.